Shi Zhengyi on China Ethnic Minority Areas Economic System Reform - Xia, Dongming; Tian, Guang (Advances in Social Sciences Research Journal, 2022)
This article introduces Professor Shi Zhengyi’s early theoretical thinking on reforming the Chinese ethnic minority economic system. Due to historical and political reasons, China’s new economic system China built a planned economic system after the founding of the People’s Republic of China. This economic system helped China develop its industries. But this rigid economic system became incompatible with product development, especially in ethnic minority areas. Ethnic minority areas were backward in production and unbalanced in development. After 1978, China gradually built its new socialist economic system, a planned commodity economy based on public ownership. In this economic system reform, the minority autonomous areas should be open to foreign countries, introduce advanced technology and investment, and develop import and export trade. At the same time, the minority autonomous areas should strengthen economic cooperation with other regions. Ethnic minority areas must also carry out comprehensive economic system reform, which should fully consider the specific characteristics of these areas, especially the ethnic and regional factors.